Analisis hukum syari'ah terhadap praktik jual beli online di Indonesia - Anom Sudibyo Raharjo; Sumadi; Muhammad Tho’in (ITB AAS INDONESIA Surakarta, 2026)
The rapid development of information technology has increased the use of online buying and selling through digital platforms. This study aims to analyze the conformity of online trading practices in Indonesia with Islamic legal principles. The research employs a normative-empirical legal method with a descriptive qualitative approach. Data were collected through observation, interviews, documentation, and library research based on the Qur’an, Hadith, DSN-MUI fatwas, and fiqh muamalah literature. The findings indicate that online transactions generally meet the essential elements and requirements of contracts in Islamic law, including the existence of sellers and buyers, the subject of the transaction, prices, and mutual consent expressed through digital media. Digital payment systems are also considered sharia-compliant as long as they do not involve elements of riba, gharar, or maysir. However, several issues remain, including inaccurate product descriptions, delivery delays, and potential fraud. Therefore, improving information transparency, consumer protection, and sharia literacy is necessary to ensure fairer and more sharia-compliant online transactions.